Students’ Perceptions of 360 Degree Virtual Tour-Based Historical Learning About The Cultural Heritage Area of The Kapitan and Al-Munawar Villages in Palembang City - Abidin, Rahman; Suryani, Nunuk; Sariyatun, . (International Journal of Social Sciences and Management, 2020)
Perception is a process of activities based on one's observations of an object that is observed in the form of responses delivered in oral or written form and can affect the value of an object being observed. Student perception is very important to be known in an assessment. The problem in this study is how students 'perceptions of the 360 ​​Degree Virtual Tour-based Historical Learning about the cultural heritage area of ​​the Kapitan and Al-Munawar villages in Palembang especially the Vocational High School of the Teachers' Association of the Republic of Indonesia 1 Palembang. The purpose of this study was to determine and students' perceptions of 360-degree virtual tour-based history learning about the cultural heritage areas of Kapitan and Al-Munawar villages in Palembang City. The research method used in this research is a descriptive qualitative method. Data collection techniques through interviews, observation, documentation and questionnaires. The Analysis Data Technique uses qualitative descriptive analysis. From the results of this study obtained data on student perceptions with an average percentage of 87%, seen from the three indicators namely receiving, understanding and assessing or responding to show that students' perceptions of choosing to agree and strongly agree with the excellent category. Thus, the mobile-based history learning model can improve the quality of learning more effectively and easily accepted by students in order to achieve better and more optimal learning outcomes. Int. J. Soc. Sc. Manage. Vol. 7, Issue-3: 105-112